KONTRIBUSI SOSIAL: Membangun Semangat demi Mewujudkan Impian Anak-Anak di Panti Asuhan Attafakur melalui Sosialisasi - Gustina, Rina; Heriyanti, Lesti (Jurnal PKM Manajemen Bisnis, 2024)
Social contribution is one of the Independent Student Exchange programs in the Nusantara module course which is carried out at the end of the Nusantara module activities. This Social Contribution Contribution was carried out at the Attafakur Orphanage which aims to build the spirit of the orphanage children in making their dreams and aspirations come true. In the implementation method there are three stages, namely opening, implementation and closing. It is hoped that the results of implementing this social contribution activity will provide enthusiasm to realize their respective dreams.